التلوث النفسي وعلاقته بالحرمان العاطفي لدى طلبة الجامعة - الدباغ, لمياء كمال عبدالله; خان, هناو حسن محمد (Sulaimani Journal for Humanities, 2021)
Psychological pollution and emotional deprivation are considered as a fundamental issue in psychology, which have negative effects on the personality, sense of comfort and psychological health of individual. This research deals with a large and important segment of society, which is university students, as they represent an active segment in society and its development. The research aims to identify the level of psychological pollution and emotional deprivation within entire sample, according to gender and specialization (scientific and humanitarian) and the relationship between them among the research sample which consists of (353) male and female students. The sample was chosen randomly within the tow universities Sulaimani and Salahaddin University. In order to achieve the aims of research, the researchers used the scale of (Al-Nawajhah, 2017) to measure the psychological pollution, and the scale of (Kadri and Boukhdina, 2016) to measure the emotional deprivation. After the verification of validity and reliability. The final implementation of measures on the sample performed and the data processed statistically using (SPSS) program. The results showed that Psychological pollution and emotional deprivation among university students was at a low significant level and there were no significant differences in the level of psychological pollution and emotional deprivation according to gender and specialization. But it was founded that there was a significant difference in the level of psychological pollution between students of the tow Universities. The psychological pollution was higher among students of Sulaimani University; about the emotional deprivation between students of Sulaimani University and Salahaddin University there were no significant differences between the two universities.
Keywords: Psychological pollution; emotional deprivation